PENELITIAN SITUS TAMBORA ANTARA PELUANG DAN TANTANGAN - I Made Geria (Balai Arkeologi Bali, 2012)
The research result obtained during research activities in Tambora can be used as reference in reconstructing the civilization of Tambora, of which is the strength owned by the Tambora Site. Apart from the strength, the opportunities and challenges in the management of Tambora Site need to be assessed. To guide this idea, a qualitative approach with a matrix or SWOT (Strength, Weakness, Opportunity, and Treats) was applied. The crucial threats and challenges are the security of the site area that is widely open and has not been accommodated in the management of land structure. However, the mobilization of the strength owned by Tambora site will be able to change the treat and challenges into opportunities, if they are synergized with the power of a vigorous publications. It can be used to as an opportunity to grow awareness of the community and regional government to be more active and improving care in the management of the Tembora site. In the future, the strength of Tembora can be of great opportunity to keep conducting research by involving various stakeholders from multidiscipline as well as from the private sectors. Hasil penelitian yang diperoleh selama kegiatan riset di Tambora dapat dijadikan acuan dalam merekonstruksi peradaban Tambora, yang merupakan kekuatan (strength) yang dimiliki oleh situs Tambora. Disamping kekuatan, perlu dikaji pula mengenai peluang dan tantangan dalam pengelolaan situs Tambora. Memandu pemikiran ini, dipergunakan analisis atau pendekatan kualitatif dengan matriks SWOT (Strength, Weakness, Opportunity, dan Threats ). Ancaman dan tantangan yang paling krusial adalah keamanan terhadap kawasan situs yang terbuka luas dan belum diakomodir dalam penataan tata ruang kawasan. Meski demikian, mobilisasi kekuatan yang dimiliki situs Tambora bisa saja merubah ancaman dan tantangan menjadi peluang, jika disinergikan dengan kekuatan publikasi yang gencar. Hal ini dapat dijadikan peluang menumbuhkan kesadaran masyarakat dan pemerintah daerah setempat untuk semakin peduli bahkan berperan aktif dalam pengelolaan Tambora. Kedepannya, kekuatan situs Tambora dapat dijadikan peluang untuk terus mengadakan riset dengan melibatkan berbagai pihak dari berbagai multi disiplin dan swasta secara terpadu.